Effectiveness of Agricultural Extension of Making Liquid Organic Fertilizer (POC) from Coconut Husk at KWT Pamelum, Hayaping Village, Awang District, East Barito Regency - Atehayati Atehayati; Budi Purwo Widiarso; Siti Nurlaela (Akademi Komunitas Perkebunan Yogyakarta, 2023)
The farmer women's group has a strategic role in improving the farming skills of its members. This study aims to analyze the effectiveness of the implementation of the agriculture extension program carried out at KWT Pamelum, Hayaping Village, Awang District, East Barito Regency with material for making liquid organic fertilizer made from coconut husk. Counseling was conducted on 30 female farmers. Measurements are carried out before and after the activity. Using Wilcoxon analysis, a significant increase in results (p = 0.00) was obtained in the value before and after the extension program. With N gain score analysis, there is an effective improvement in both knowledge, attitudes, and skills. These results are then implemented in shared gardens at KWT. It is expected that extension workers will assist farmers to continue to apply the use of liquid organic fertilizer in their farming because the results are proven to be better and safer.